A Factor Analytic Assessment of Financial Sustainability: The Case of New South Wales Local Government. Issue 2 (16th June 2016) - Drew, Joseph; Dollery, Brian
Abstract : Financial sustainability in local government remains a pressing problem which has seen a host of public policy interventions, including compulsory consolidation and performance monitoring through financial sustainability ratios. In September 2014, the New South Wales (NSW) Government announced a reform program centred on increasing scale in local government to make councils 'fit for the future'. We apply factor analysis to the financial ratios informing the NSW Government's reform initiative to identify the underlying factors for observed financial performance data. We find evidence indicating that three independent underlying factors account for the adopted measures of financial sustainability. The public policy implication arising from this study suggests that the reforms imposed by the NSW Government on NSW municipalities may only meet with limited successa.